Study of online reviewers in a UGC community - Phyu Mon Theint (2014)
The rise of web 2.0 and social media gave voice to Internet users to air their opinions through a lot of ways. One of the ways they do so is through the form of user generated content (UGC). As user generated content gains popularity, contributors online form communities through their contributions. As they continue contributing in the community, a portion of general users mature through their contributions and become mature reviewers (Porter, 2008). This study attempts to examine the stages of maturity of the reviewers in a user generated content website. The study is motivated by prior research which revealed that users are keener to trust reviews contributed by credible reviewers (Awad & Ragowsky, 2008). Reviewers who have matured through their contributions as mentioned before are usually considered credible due to their constant participation and exposure to the community (Dellarocas, 2003). Since reviews by these reviewers have an impact on the product performance itself, it is useful for organizations to learn about the attributes of the credible reviewers (Clemons, Barnett, & Appadurai, 2007). Although attributes of reviewer credibility has been covered by previous research, little research is available that address lifecycle of the reviewers themselves as they mature. Thus, this study seeks to understand how review characteristics, in particular, ratings, helpfulness and readability changes over time for mature reviewers as well as how they differ for different rates of maturity. Research will be done on how the reviewers mature over time as well as how they differ in their behaviors in maturity In this study, stages of maturity will be broken down into initial, intermediate and mature. The stages are defined by the number of reviews contributed by each reviewer. The idea of this study stems from the research of McAuley & Leskovec (2013) that states different reviewers at different maturity stages adopt different behavior. In particular, the study uncovered significant variation in rating patterns, helpfulness and readability. Imdb.com was selected as a source for the dataset in this research due to its abundance of existing data since the website has been in existence for over 20 years. The volume itself will stand as a good source for sampling. In addition, since the study intends to focus on the portion of reviewers that have matured, basing the study on the prolific reviewers by the imdb website (those who have contributed at least a thousand reviews) will be deemed justifiable compared to randomly selecting reviewers from other communities. From the result of study, it was found that frequent reviewers tend to write more critical appraisal of the movies while intermittent reviewers tend to write more personal and affective reviews. In terms of writing style, intermittent reviewers are more careful about the choice of words and structure of their reviews while the frequent reviewers focus more on the analysis of the movies. Readability of the intermittent reviewers experiences a steeper progress while their counterparts experience less obvious progress. Across the three stages of maturity, helpfulness and readability improve over time while rating tends to converge towards the average ratings of all other reviewers.